An investigation of contact characteristics of a roller bearing with a subsurface crack. (October 2020) - Liu, Jing; Li, Xinbin; Shi, Zhifeng
Highlights: A FE model for a roller bearing with the horizontal and slant subsurface cracks is developed. Effects of the horizontal and slant subsurface cracks on the contact characteristics in a roller bearing are studied. The mathematic relationship between the contact characteristics and crack sizes is obtained. Abstract: Roller bearings are widely used in various rotating machineries. A main failure mode of the roller bearings is the subsurface crack due to the contact fatigue, which can produce large spalling. An investigation of the contact characteristics of the bearings with the subsurface crack may be helpful for the incipient fault detection, which were not reported in the previous works. To overcome this problem, this study presents a finite element model to study the effects of the horizontal and slant subsurface cracks on the contact characteristics in a roller bearing. The relationship between the contact deformation and crack sizes (length, depth, and slope angle) is obtained, as well as that between the contact zone width and crack sizes. The mathematic relationship between the contact characteristics and crack sizes is obtained by using a polynomial fitting approach. Note that the crack length, depth, and slope angle will affect the contact characteristics of the bearing. The results provide that the established approach can give a useful numerical method for analyzing the contact characteristics of a roller bearing with the horizontal and slant subsurface cracks.